The Effect of Training on The Performance of Micro, Small, and Medi-um Enterprises (MSMES) Employees Through The Support of The Genpro Organization as A Mediator - Iwan Kurniawan; Asep Saifudin; Deni Gustiawan; Mulyadi Mulyadi (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the effect of training on employee performance in Micro, Small, and Medium Enterprises (MSMEs) through the support of the Genpro organization as a mediator. The research employs a quantitative approach with data collection techniques including questionnaires and documentation. The sample consists of MSME employees involved in training programs facilitated by Genpro. Data analysis is conducted using Structural Equation Modeling (SEM) to test the relationships between training, organizational support, and employee performance. The results indicate that training directly affects employee performance, and Genpro's organizational support plays a significant role as a mediator in this relationship. These findings highlight the importance of organizational support in maximizing training effectiveness within the MSME context. The implications of this study can assist stakeholders in designing more effective training programs and supporting employee development in MSMEs.